2016
DOI: 10.1007/s00405-016-4023-4
|View full text |Cite
|
Sign up to set email alerts
|

Pleomorphic adenoma in the nasal cavity: a clinicopathological study of ten cases in Finland

Abstract: The objective of the study was to investigate the nationwide occurrence of sinonasal pleomorphic adenoma in Finland. A retrospective study was conducted at The Departments of Otorhinolaryngology-Head and Neck Surgery, and Pathology at the five university hospitals in Finland. Data were obtained by searching for sinonasal pleomorphic adenoma cases in the clinical and histopathological registries at these institutions for the past two to four decades. All patients who had had a histologically proven pleomorphic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 20 publications
0
14
0
5
Order By: Relevance
“…Sinonasal pleomorphic adenomas have more cytoplasm and predominant epithelial components which differs them from mixed neoplasms of major salivary glands, also they are devoid of capsules and have few stromal components. 8 Vento et al reported cases of benign Pleomorphic adenoma of the nasal cavity, which were surgically resected and presented with no recurrence during various follow-up periods. 8,10 Another study stated that the abnormal origin of Pleomorphic adenoma from the nasal septum mucosa may be caused by dislocated embryonic epithelial cells which arises from the ectoderm and carried into the septal region via the nasal pits.…”
Section: Discussionmentioning
confidence: 99%
“…Sinonasal pleomorphic adenomas have more cytoplasm and predominant epithelial components which differs them from mixed neoplasms of major salivary glands, also they are devoid of capsules and have few stromal components. 8 Vento et al reported cases of benign Pleomorphic adenoma of the nasal cavity, which were surgically resected and presented with no recurrence during various follow-up periods. 8,10 Another study stated that the abnormal origin of Pleomorphic adenoma from the nasal septum mucosa may be caused by dislocated embryonic epithelial cells which arises from the ectoderm and carried into the septal region via the nasal pits.…”
Section: Discussionmentioning
confidence: 99%
“…El tamaño del tumor descrito en la literatura es variable pudiendo ir desde los 5 mm hasta los 7 cm 2,7,12 e incluso hay reportes de mayores dimensiones llegando hasta 10 cm 8,15 . La edad de presentación puede ir desde la niñez a la adultez observándose una mayor concentración de casos entre la tercera y sexta década de la vida 1,2,5,7,9,11 con ligero predominio en mujeres 1,6,7,10,11,16 .…”
Section: Discussionunclassified
“…The average age of the affected patients was 55.7 years, approximately a decade older than the average age of patients with PA of the nasal cavity. [26] All reported cases have involved a surgical procedure as an initial treatment modality, such as a wide excision through lateral rhinotomy, partial or medial maxillectomy, or craniofacial resection. However, the unique presentation of a pedunculated, well-encapsulated nasal mass in our patient resulted in our utilizing a wide endoscopic excision.…”
Section: Discussionmentioning
confidence: 99%